X-irradiation-induced changes in the diffusion parameters of the developing rat brain - Syková, E; Svoboda, J; Simonová, Z; Lehmenkühler, A; Lassmann, H (Neuroscience, 1996)
Three diffusion parameters of brain tissue, extracellular space volume fraction (alpha), tortuosity (lambda) and non-specific uptake (kappa') of tetramethylammonium were studied in the somatosensory neocortex and subcortical white matter of the rat during postnatal development (postnatal days 2-21) after X-irradiation at postnatal days 0-1. The diffusion parameters were determined from extracellular concentration-time profiles of tetramethylammonium. The tetramethylammonium concentration was measured in vivo with ion-selective microelectrodes positioned 130-200 microns from an iontophoretic source. X-irradiation with a single dose of 40 Gy resulted in typical early morphological changes in the tissue, namely cell death, DNA fragmentation, extensive neuronal loss, blood-brain barrier damage, activated macrophages, astrogliosis, increase in extracellular fibronectin and concomitant changes in all three diffusion parameters. The changes were observed as early as 48 h post-irradiation (at postnatal days 2-3) and still persisted at postnatal day 21. On the other hand, X-irradiation with a single dose of 20 Gy resulted in relatively light neuronal damage and loss, while blood-brain barrier damage, astrogliosis and changes in diffusion parameters were not significantly different from those found with 40 Gy. It is known that the volume fraction of the extracellular space in the non-irradiated cortex is large in newborn rats and diminishes with age [Lehmenkühler A. et al. (1993) Neuroscience 55, 339-351]. X-irradiation with a single dose of 40 or 20 Gy blocked the normal pattern of volume fraction decrease during postnatal development, and in fact brought about a significant increase. At postnatal days 4-5, alpha increased to 0.49 +/- 0.036 in layer III, 0.51 +/- 0.042 in layer IV, 0.48 +/- 0.02 in layer V, 0.48 +/- 0.028 in layer VI and 0.48 +/- 0.025 in the white matter. The large increase in alpha persisted three weeks after X-irradiation. Tortuosity and non-specific uptake decreased significantly at postnatal days 2-5; at days 8-9 they were not significantly different from those of control animals, while they increased significantly at days 10-21. Less pronounced but significant changes in all three diffusion parameters were also found in areas in the ipsilateral hemisphere adjacent to directly X-irradiated cortex. Compared to the control animals [Lehmenkühler A. et al. (1993) Neuroscience 55, 339-351], a significant decrease of alpha, lambda and kappa' was found in the contralateral hemisphere 48-72 h after X-irradiation. Later, alpha values were not significantly different from those in control animals. The decrease in lambda persisted at postnatal days 4-5. A significant increase in lambda and kappa' was found at postnatal days 18-21. We conclude that X-irradiation of the brain in the early postnatal period, even when it results in only relatively light damage, still produces changes in all three diffusion parameters, particularly a large increase in extracellular space volume fraction in all cortical layers, and in the subcortical white matter. Such changes in extracellular volume fraction of the brain can contribute to impairment of signal transmission, e.g. by diluting ions and neuroactive substances released from cells, and can play an important role in functional deficits, as well as in the impairment of developmental processes. Moreover, the increase in tortuosity (inferred from the decrease in apparent diffusion coefficient) in the X-irradiated cortex, as well as in the contralateral hemisphere, suggests that, even when extracellular volume is large, the diffusion of the substances is substantially hindered.
Keywords: mozek; krysa rodu Rattus; Animals, Newborn; Animals; Rats, Wistar; extracelulární prostor; imunohistochemie; Extracellular Space; potkani Wistar; Immunohistochemistry; zvířata; novorozená zvířata; Brain; Rats